Análisis espacial de la dispersión del contaminante atmosférico dióxido de azufre emitido por la fabricación de ladrillos en la vereda de Patio Bonito, municipio de Nemocón, Cundinamarca - Colombia (2022)
Two estimates of the dispersion of the atmospheric pollutant sulfur dioxide (SO2) were developed for the brick kiln La Fe, located in the village of Patio Bonito in the municipality of Nemocón, taking into account the two predominant atmospheric stabilities, according to the climatological conditions of the area of interest, using as main input reference data found in different degree projects, internet and public entities such as IDEAM, and assigning high hypothetical values to the most unstable atmospheric stability, thus allowing to gather the parameters required for the development of the Gaussian model of dispersion. The models were made with the use of the "Model Builder" which allowed to obtain as a result in raster format the concentrations dispersed throughout the emission source. The result for type C atmospheric stability yielded a maximum concentration of the pollutant of interest of 2.59x10-4 μ/m3 , while for type B atmospheric stability it was 1.59x10-4 μ/m3 . The lowest values for each atmospheric stability were below 1x10-6 μ/m3